Factors associated with receipt of informal care among the Vietnamese older persons: Evidence from a national survey - Long Thanh Giang; Nam Truong Nguyen; Tham Thi Hong Pham; Phong Manh Phi (Frontiers Media S.A., 2023)
BackgroundThe rapidly growing older population in Vietnam poses an increasing need for care among the older persons, who have mainly relied on informal care at homes and communities. This study examined the Vietnamese older persons' individual and household factors determining their receipt of informal care.MethodsThis study provided cross-tabulations and multivariable regression analyses to identify who provided assistance to the Vietnamese older people along with their individual and household characteristics.DataThe nationally representative survey on older persons, namely Vietnam Aging Survey (VNAS) in 2011 was used in this study.ResultsWe found that proportions of older persons having difficulty in activities of daily living (ADLs) were different in regard to their age, sex, marital status, health status, working status, and living arrangements. In care provision, gender differences were clear, in which females generally had significantly higher rates of providing care to older persons than their male counterparts.ConclusionCare for older persons in Vietnam has been mainly provided by their families, and thus changes in socio-economic, demographic factors along with differences among generations in family values will be a key challenge to maintain such care arrangements.